On the application of selected exploratory data analysis methods to assess differences in the level of sustainable development in the environmental domain of voivodships in Poland - Małgorzata Misztal (Economic and Environmental Studies (E&ES), 2018)
The purpose of the study was to assess the differences in the level of sustainable development in environmental domain of voivodships in Poland in the years 2008-2015. Seven indicators belonging to 3 areas of the environmental domain (energy, air protection, waste management) were analysed with the use of principal component analysis (PCA) and the between-class PCA. The results revealed large differences between voivodships mainly due to the level of air pollutants emissions from plants especially noxious to air purity. It has also been shown that in the years 2008-2015 a visible increase in the outlays on fixed assets serving environmental protection and development of ecological awareness of society was observed.
Keywords: C02; C38; R11; 330; sustainable development; environmental domain; multivariate exploratory data analysis; principal component analysis